A five-finger mnemonic for teaching schoolchildren the theoretical components of adult basic life support: a modified reactive Delphi-guided development and memorability pilot test with schoolchildren - Nino Fijačko; Robert Greif; Špela Metličar; Gregor Štiglic; Benjamin S. Abella; Matej Strnad; the Delphi study investigators (BMC Medical Education)
Abstract Background A mnemonic is a cognitive aid frequently used in health-related education. The main goal of this study was to develop and test a 5-finger mnemonic for teaching schoolchildren the theoretical aspects of adult Basic Life Support (BLS) steps, a process rarely described in the context of instructing laypersons. Methods Experts from the European Resuscitation Council’s Basic Life Support Science and Education Committee (ERC BLS SEC), specializing in teaching adult BLS, participated in the first phase of the pilot study. This phase employed the modified reactive Delphi to develop a 5-finger mnemonic for teaching schoolchildren the theoretical aspects of adult BLS steps, in accordance with the 2021 ERC BLS guidelines. The mnemonic underwent revision rounds based on expert suggestions and was evaluated using a 9-point Likert scale. The process was repeated until there was unanimous approval. In the second phase, a pilot test was conducted with schoolchildren at a summer camp to assess their recall of the 5-finger mnemonic. Following their training in adult BLS steps utilizing the 5-finger mnemonic, schoolchildren were tasked with arranging cards depicting images from the mnemonic both before and after the training. Results From March to October 2022, a four-round modified reactive Delphi engaged four experts from the ERC BLS SEC. Initial expert consensus was moderate, 6.0 (IQR = 4.5–7.5, min = 1, max = 9), on a scale 1 (“totally disagree”) to 9 (“totally agree”). The experts consensus improved over subsequent rounds, resulting in two final versions of the 5-finger mnemonic. Both versions concentrate on the comprehensive adult BLS, differing only in their approach to cardiopulmonary resuscitation (CPR): one employs a method of 30 chest compressions followed by two rescue breaths, while the other utilizes compression-only CPR. In August 2023, a recall pilot test involved mostly female schoolchildren (12/13, 92.3%). Pre-training, no cards with 5-finger mnemonic content were arranged correctly, but post-training, progress improvement was observed, especially in older schoolchildren (Z = -2.727, p = 0.006). Conclusions The pilot study highlights the potential of using tailored educational tools, such as mnemonics, to teach important lifesaving skills to different age groups. This suggests that the 5-finger mnemonic effectively improved schoolchildren’s understanding of the theoretical aspects of adult BLS steps.